Effect of High Frequency Pulsing on the Interfacial Structure of Anodized Aluminium-TiO2. Issue 7 (1st January 2015) - Gudla, Visweswara Chakravarthy; Jensen, Flemming; Bordo, Kirill; Simar, Aude; Ambat, Rajan
Abstract : High frequency anodizing of friction stir processed Al-TiO2 surface composites was investigated. The effect of anodizing parameters on the structure and morphology of the anodic layer including the incorporation of the TiO2 particles into the anodic layer is studied. Anodizing process was carried out using a high frequency pulse and pulse reverse pulse technique at a fixed frequency in a sulfuric acid bath. The structure of the composites and the anodized layer was studied using scanning and transmission electron microscopy. The pulse reverse pulse anodizing technique, using a negative potential on the low voltage cycle, showed extensive pore branching and pore generation at the TiO2 particle-anodic alumina matrix interface. However, the pulse anodizing technique using zero potential during the low voltage cycle showed no such features in the pore morphology, but only entrapment of TiO2 particles into the anodic alumina. Lower electrical resistance of the TiO2 arising from oxygen defects, combined with applied negative potential during the low voltage cycle, are found to be responsible for the observed morphological features in the anodic alumina.